2019
DOI: 10.1186/s12882-019-1517-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation as a diagnostic biomarker of rare renal diseases: a systematic review

Abstract: Background The challenges in diagnosis of rare renal conditions can negatively impact patient prognosis, quality of life and result in significant healthcare costs. Differential methylation is emerging as an important biomarker for rare diseases and should be evaluated for rare renal conditions. Methods A comprehensive systematic review of methylation and rare renal disorders was conducted by searching the electronic databases MEDLINE, EMBASE, PubMed, Cochrane Library, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Epigenetic signatures may display tissue specificity linked to disease mechanisms, however, obtaining kidney biopsy material is invasive and is not performed as part of routine clinical practice in people with DKD and T1D in the United Kingdom. Peripheral blood-based methylation biomarkers have shown promise in several clinical fields ( Moore et al, 2014 ; Agha et al, 2019 ; Cardenas et al, 2019 ; DiTroia et al, 2019 ; Henderson-Smith et al, 2019 ; Kerr et al, 2019a , b , 2020 ; Ladd-Acosta and Fallin, 2019 ; Zhou et al, 2019 ) including kidney disease ( Smyth et al, 2014b , 2018 ; Swan et al, 2015 ; Aranyi and Susztak, 2019 ; Gluck et al, 2019 ; Kato and Natarajan, 2019 ; Kerr et al, 2019b ; Park et al, 2019 ). We have previously demonstrated that blood-derived differential methylation is also reflected in kidney-derived differential methylation for CKD ( Smyth et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic signatures may display tissue specificity linked to disease mechanisms, however, obtaining kidney biopsy material is invasive and is not performed as part of routine clinical practice in people with DKD and T1D in the United Kingdom. Peripheral blood-based methylation biomarkers have shown promise in several clinical fields ( Moore et al, 2014 ; Agha et al, 2019 ; Cardenas et al, 2019 ; DiTroia et al, 2019 ; Henderson-Smith et al, 2019 ; Kerr et al, 2019a , b , 2020 ; Ladd-Acosta and Fallin, 2019 ; Zhou et al, 2019 ) including kidney disease ( Smyth et al, 2014b , 2018 ; Swan et al, 2015 ; Aranyi and Susztak, 2019 ; Gluck et al, 2019 ; Kato and Natarajan, 2019 ; Kerr et al, 2019b ; Park et al, 2019 ). We have previously demonstrated that blood-derived differential methylation is also reflected in kidney-derived differential methylation for CKD ( Smyth et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…4) V collagen and protein leakage has been reported in correlation with GFR and their presence in urine may be considered as the novelty for the diagnostic approach  Glomerular Protein-Microglobulin and N Glucosaminidase and Alanine aminopeptidase are the glomerular proteins and their dysfunction can be indicated as the sign of Fabry renal impairment (Fig. 4) [5].…”
Section: Fig 4 Potential Marker For Diagnosismentioning
confidence: 99%
“…Fabry disease is a rare renal disorder caused by mutation of the X-linked GLA gene which results in the deficiency of alpha-galactosidase [1]. The cells which are deficient in the alphagalactosidase enzyme can not metabolize glycosphingolipid mainly Globotriaosylceramide (GB 3 ) [2][3][4][5][6][7]. Accumulation of GB 3 can lead to various symptoms and for the progression of the cascade (series of progressive events) rather than deficiency of enzymes so maybe a diagnostic tool for the detection of Fabry disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lysine methylation is one of the most important post‐translational modifications (PTMs) of proteins because it regulates various biological processes including cell growth, division, gene expression, and DNA/RNA binding [1–5] . Due to lysine's unique structure, it has the ability to undergo mono, di, and tri methylation, and different levels of methylation give rise to different functions and localization within a cell [6] . PTMs regulate cellular processes by influencing the interactions of proteins with other proteins, nucleic acids, and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Due to lysinesu nique structure,i th as the ability to undergo mono, di, and tri methylation, and different levels of methylation give rise to different functions and localization within acell. [6] PTMs regulate cellular processes by influencing the interactions of proteins with other proteins,n ucleic acids,a nd lipids.W efocused our attention particularly on monomethyl lysine (Kme) PTM, which occurs on both histones and nonhistone proteins. [7][8][9][10][11] Kme PTMs have been implicated not only in transcriptional activation and silencing but the aberrant PTM levels have been linked to numerous diseases and disorders such as heart disease,cancer, and diabetes.…”
Section: Introductionmentioning
confidence: 99%